Motivation factors that enhance KTMB employees' job performance specifically for commuter unit in Klang Valley / Abdul Azim Zainal Abidin - Zainal Abidin, Abdul Azim (Faculty of Business and Management, 2007)
Keretapi Tanah Melayu (KTMB) or the Malayan Railway is the main rail operator in Peninsular Malaysia. Basically, the research objectives of this study are to identify whether the intrinsic factors for example achievement, recognition, personal growth, job descriptions have significant relationship among KTMB employees. Besides that, the study also wanted to clarify whether the extrinsic motivational factors for example payment, promotion, working condition and job security have significant relationship on the level of job performance among the employees specifically in Commuter unit. Moreover, the research objectives of this study are to provide appropriate recommendation when dealing with demotivated employees.